2022
DOI: 10.1002/pol.20220122
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous carbons from self‐assembled polymers

Abstract: Polymer self-assembly provides a robust and cost-efficient nanomanufacturing platform for enabling a broad range of applications, such as microelectronics, drug delivery, and separation membranes. This review focuses on discussing the progress and opportunities of self-assembled polymer in the synthesis of mesoporous carbons (MCs), which have aroused significant research interests over the past decades. Specifically, we will discuss the two most established approaches for converting nanostructured polymers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 269 publications
0
13
0
Order By: Relevance
“…Ordered mesoporous carbons (OMCs), containing pores with sizes ranging from 2 to 50 nm, have attracted tremendous attention in both fundamental and applied research 1 . These materials have distinct advantages over traditional microporous carbons, including synthetic flexibility in tuning the pore size and matrix chemistry, uniform pore structures with excellent accessibility, and enhanced mass transport within the pore channels 2 . These favorable properties of OMCs enable their broad applications in diverse fields, such as energy storage 3 , 4 , water remediation 5 , catalyst supports 6 , 7 , and biomedicines 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ordered mesoporous carbons (OMCs), containing pores with sizes ranging from 2 to 50 nm, have attracted tremendous attention in both fundamental and applied research 1 . These materials have distinct advantages over traditional microporous carbons, including synthetic flexibility in tuning the pore size and matrix chemistry, uniform pore structures with excellent accessibility, and enhanced mass transport within the pore channels 2 . These favorable properties of OMCs enable their broad applications in diverse fields, such as energy storage 3 , 4 , water remediation 5 , catalyst supports 6 , 7 , and biomedicines 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This multiple-step process can be time consuming and costly. Alternatively, OMCs can be prepared by leveraging the self-assembly behaviors of surfactants and/or polymers 2 . For example, soft-templating method is widely employed for OMC fabrication, utilizing the cooperative assembly between a carbon precursor and an amphiphilic polymer/surfactant template 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is essential to choose a precursor that will lead to the final inorganic porous structure having a sufficient mechanical strength. Several combinations of block copolymers and precursors have been successfully utilized to produce ordered mesoporous structures [ 101 ]. The polyphenolic resin resol is a popular precursor for producing mesoporous carbon materials, while mesoporous silica is often produced using tetraethyl orthosilicate (TEOS) as a precursor.…”
Section: Emerging Porous Membranesmentioning
confidence: 99%
“…Outside of doping purposes, Zhou et al reported that well-controlled mesopores were formed from conventional annealing of electrospun PAN- b -PMMA fibers via BCP assembly. 96 Given the recent progress on the variety of polymer chemistry to fabricate mesoporous carbon 97 and the demonstration of time-efficient pyrolysis via RTA, 80 the opportunity in patterning via self-assembly is foreseen to arise. Such success in spatially controlled doping (both in-plane and out-of-plane) lays a great foundation for spin-on formation of p–n junctions by using different dopants for each block.…”
Section: Opportunities To Move the Field Forwardmentioning
confidence: 99%